Pengaruh Penerapan E-Samsat dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor (Studi Kasus Pada Wajib Pajak di Samsat Kota Bandung) - Rini Susanty; Vinny Stephanie Hidayat (Universitas Widyatama, 2023)
Population growth continues to increase every year, impacting the need for community mobilization so that users of transportation equipment increase. Along with the increasing amount of transportation, it is a trigger for increasing regional income, one of which is from motor vehicle taxes. Supposedly, taxpayers who did a payment on their motor vehicle tax will increase. However, compliance with payment of motor vehicle taxes has decreased in the West Java region. This suggests that the payment of vehicle taxes is still poorly respected. In this research, we are conducting explanatory research using quantitative methods. This study explores the causal relationship between E-SAMSAT application and sanctions imposition on motor vehicle tax compliance. We used a simple random sampling in the form of non probabilitiy as sampling technique. In this study, a questionnaire was utilized as a data collecting tool. Measuring respondents' opinions using a 4-point Likert scale. According to the study's findings, the better E-SAMSAT is implemented and the more stringent the tax penalties are, the more tax compliance will continue to increase. We can draw the conclusion that variable tax sanctions and variable E-SAMSAT implementation both have an effect on taxpayer compliance to some extent.